Innovative formulation and characterisation of grease made from waste engine oil - Muhammad Auni, Mauliduni; Mohd Aizudin, Abd Aziz; Nurul Waheeda, Abdu Rahman; Mohd Azmir, Arifin; Khairuddin, Md Isa; Umi Fazara, Md Ali (UPM Press, 2023)
Lubricating grease is usually produced from mineral oil, making the relationship between grease and mineral oil unavoidable. Formulation of grease from waste oil can reduce the dependency of the grease industry on mineral oil as well as help to reduce the waste generation of used oil. This study aims to produce fumed silica (FS) grease from waste engine oil (WEO) and analyse the properties of the formulated grease. The method started with treating WEO to remove any contaminants in the used oil. After that, the greases are produced using a weight percentage ratio before being examined for consistency, oil separation, oil bleeding, FTIR (Fourier transform infrared spectroscopy) analysis, and corrosiveness. In terms of uniformity, oil separation, and oil bleeding, WEO percentage content had a substantial impact on the findings. The FTIR demonstrated that synthetic greases had the same spectra when evaluated between 500 cm-1 and 4000 cm-1. The grease's corrosiveness is low, as determined by class 1 corrosiveness toward the copper strip. However, the grease properties differ when consistency, oil bleeding and oil separation test is done. Higher oil content in grease produced high oil bleeding and separation but low consistency. As a conclusion of the results, fumed silica grease with oil percentages of 83 and 82 have the most grease-like features, showing that the grease fits the traits' requirements. Based on the investigation's findings, it was established that WEO may be used as a base oil in grease formulation and that the grease's properties are satisfactory.